Distance Learning-marketing Challenges - Begum, Mustiary (Indian Journal of Marketing, 2005)
Marketing is an ongoing system . It is much more than selling and advertising. It does not operate only when something special is needed from the public at a given moment. Educational marketing is the need of the time. Education marketing is a subject with very wide coverage . It is a planned and systematic two way process of communication between an educational institution and its internal and external public designed to build goodwill, understanding and support for that organization. Education, like most 'pure' services is an intangible dominant service. 'Let the market decide ' - Darwin's principle holds good even today because it is only the fittest that would survive. Existing educational institutions that were created to meet the needs of the society are fast disappearing . We need new educational organizations that can exploit the new technologies, harness the power of multimedia communications as an alternative to the traditional mode of face-to-face presentations in a physical classroom. One of the oldest and largest efforts of this nature is the Open University in Great Britain. Distance education/learning as the basic approach in the Open University systems in a number of developing countries has acquired considerable significance in promoting both educational and professional well-being of the community through new communication technologies (Aslam ,1994).